Diet analysis of Hazel dormouse (Muscardinus avellanarius), and best practice for studies combining DNA and micro-histologic analysis of faecal samples - Sussie Pagh; Hanne Lyngholm Larsen; Sara Sofie Bertelsen; Heidi Holm Hansen; Helle Vilhelmsen; Cino Pertoldi; Nadieh de Jonge (Mammal Research, 2026)

Exposure of European hares (Lepus europaeus) to pesticides in Danish agricultural areas - Elena Hakme; Sussie Pagh; Victor Manuel Cutillas; Sara Haydar; Mette Sif Hansen; Hanne Lyngholm Larsen; Peter Roslev; Mette Erecius Poulsen (Environmental Pollution, 2025)

Diet of raccoon dogs (Nyctereutes procyonoides) in Danish wetlands with focus on ground-nesting birds and amphibians - Sussie Pagh; Nadieh de Jonge; Stine Karstenskov Østergaard; Cino Pertoldi; Brittany Wooldridge; Anders Mebus Laustsen; Jens-Christian Svenning; Morten Foldager Pedersen; Hanne Lyngholm Larsen; Jeppe Lund Nielsen; Søren Toft (European Journal of Wildlife Research, 2025)

Gross pathology and liver mercury concentrations in harbour porpoises, harbour seals and grey seals in Denmark, Northern Europe - Christian Sonne; Aage K.O. Alstrup; Sussie Pagh; Charlotte Bie Thøstesen; Trine Hammer Jensen; Tim Kåre Jensen; Anders Galatius; Line Kyhn; Jens Søndergaard; Ursula Siebert; Jan Lakemeyer; Rune Dietz (Science of The Total Environment, 2024)

Habitat selection and movement patterns of the Raccoon dog (Nyctereutes procyonoides) in Denmark using GPS telemetry data - Brittany Wooldridge; Jens-Christian Svenning; Sussie Pagh (European Journal of Wildlife Research, 2024)
The Asiatic raccoon dog ( Nyctereutes procyonoides) has successfully colonized Northern, Eastern, and Central Europe, following 20 th century introductions. While subject to eradication campaigns, its ecological impacts remain incompletely understood and debated. This study aims to examine the habitat preference and movement patterns of raccoon dogs in Denmark using GPS telemetry data. Habitat selection patterns were examined seasonally using Jacob’s electivity index. Movement intensity (travel speed) was examined according to temporal and environmental predictors such as time of day, time of year and habitat type. Raccoon dogs showed an overall preference for peatbogs, marshes, and broadleaf tree cover, and an overall avoidance of water bodies (per se), artificial surfaces and constructions, natural material surfaces (e.g., river pebble banks, beaches, sand dunes), cultivated areas, coniferous tree cover and herbaceous vegetation, and a close to neutral selection pattern for moors and heathland. Habitat usage was generally consistent throughout the seasons for all habitat types, apart from minor shifts observed, particularly from November to February. The raccoon dog exhibited a unimodal nocturnal activity pattern throughout all seasons, with highest mean travel speeds occurring during spring and lowest during winter. Prolonged periods of higher mean daily speeds were observed during autumn. Mean speed levels also varied according to habitat type, with raccoon dogs moving slower in habitats they preferred and faster in those they did not prefer. These results indicate that raccoon dogs in Denmark adjust their habitat selection and movement patterns throughout the year, with a general preference for moist and high tree coverage areas. This information can be utilized in forecasting models for their potential future range and area use in different regions.

Can reintroduction of beavers improve insect biodiversity? - Line Holm Andersen; Christian Ransborg; Cino Pertoldi; Sussie Pagh; Simon Bahrndorff (Journal of Environmental Management, 2023)

Prevalence of Toxoplasma gondii and Cryptosporidium in Feral and Farmed American Mink (Neovison vison) in Denmark - Mita Eva Sengupta; Sussie Pagh; Anna-Sofie Stensgaard; Mariann Chriel; Heidi Huus Petersen (Acta Parasitologica, 2021)

Comparing DNA metabarcoding with faecal analysis for diet determination of the Eurasian otter (Lutra lutra) in Vejlerne, Denmark - Cino Pertoldi; Jakob Braüner Schmidt; Patrick Møller Thomsen; Louise Bach Nielsen; Nadieh de Jonge; Laura Iacolina; Federico Muro; Kristian Trøjelsgaard Nielsen; Sussie Pagh; Torben Linding Lauridsen; Line Holm Andersen; Erika Yashiro; et al. (Mammal Research, 2021)

Modelled population growth based on reproduction differs from life tables based on age determination in Danish raccoon dogs (Nyctereutes procyonoides) - Sussie Pagh; June Buxbom; Mariann Chriél; Cino Pertoldi; Jes Søe Pedersen; Mette Sif Hansen (Mammal Research, 2020)

The diet of Danish red foxes (Vulpes vulpes) in relation to a changing agricultural ecosystem. A historical perspective - Sussie Pagh; Rune Skjold Tjørnløv; Carsten Riis Olesen; Mariann Chriel (Mammal Research, 2015)